Experimental Study on Thawing of Frozen Lamb with High Voltage Electrostatic Field - Tang Shupei; Li Baoguo; Gao Zhixin (Zhileng xuebao)
In order to improve the thawing rate and decrease the oxidation deterioration of frozen meat during thawing process, a high voltage electrostatic thawing device was designed, and frozen lamb thawing was studied using the thawing device. The results indicate that with the increasing of electric field intensity, thawing time and juices loss was decreased, the growth of bacteria was inhibited, the color and luster of lamb thawing was improved. Compared with that without high voltage electrostatic field, when the electric field intensity was 12.5 kV/m, the time of thawing frozen lamb was shorten 11.1%, the rate of juices loss was decreased 49.6%, the total microbial counts reduced an order of magnitude and the appearance of lamb was fresh, color and luster difference was obvious. This study provides a new method for improving efficiency and quality of lamb thawing.